Impact of standard nutrition therapy and medical nutrition therapy on the immune status i.e. complement C3 and C4 in severely acute malnourished children - Dias, Bina F.; Yadav, Sneha (International Journal of Research in Medical Sciences, 2017)
Background: The objective of this study is to scientifically study and assess the levels of C3 and C4 in SAM children pre-and post-supplementation with MNT and SNT. Methods: In this comparative study we have analyzed C3 in 40 severely acute malnourished children pre and post medical nutrition therapy (MNT) and 35 severely acute malnourished children pre and post standard nutrition therapy (SNT) in the age group of 1 month to 3 years and C4 in 40 severely acute malnourished children pre and post medical nutrition therapy (MNT) and 35 severely acute malnourished children pre and post standard nutrition therapy (SNT) in the age group of 1 month to 3 years at LTM medical college and general hospital. C3 and C4 were analyzed by immunoturbidimetric assay method on RX Daytona analyzer. Results: The level of C3 was significantly low prior to the supplementation which increased after nutrition therapy, in both the groups. However, C4 levels decreased in both the groups. This decreased was found to be significant. The decrease of C4 in children supplemented with MNT was greater than those supplemented with SNT children. Conclusions: The values of C3 which increased after supplementation and the decreased values of C4 after supplementation were more significant in the MNT group this confirms MNT is a better therapy for curing malnutrition than that of the SNT.